Gasoline engine tail gas purification three-way catalyst and preparation method thereof

By using precious metal components such as Pt, Pd and Ru in the three-way catalyst, combined with Ba-modified Al2O3 and Co-Ni-Mg-Ce-Zr composite oxide materials, the problems of NH3 emission and Rh substitution in the prior art are solved. , achieving efficient and low-cost exhaust purification effect.

CN119406424AActive Publication Date: 2025-02-11CHINA FAW CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411388135.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-11
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing three-way catalysts are not effective in treating NH3 emissions in exhaust gases, and the high cost and expensive alternatives of Rh are difficult to achieve performance replacement.

Method used

Pt and Pd are used as active components of the first coating, Ru is used as active components of the second coating, and the catalytic effect is enhanced by Ba modification of Al2O3 material and Co-Ni-Mg-Ce-Zr composite oxide material. Completely replace Rh and reduce NH3 emissions.

Benefits of technology

The direct decomposition of the by-product NH3 is achieved, which reduces the emission of NH3 in the exhaust gas, while reducing the cost of the catalyst and maintains the efficient performance of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005072038470000121
    Figure BDA0005072038470000121
Patent Text Reader

Abstract

The invention provides a gasoline engine tail gas purification three-way catalyst and a preparation method thereof.The gasoline engine tail gas purification three-way catalyst comprises a catalyst carrier and a coating coated on the carrier, the coating comprises a first coating and a second coating, the first coating comprises an active component Pt, Pd and Ba modified Al2O3 material, and the second coating comprises a second coating and a third coating. And the second coating is prepared from an active component Ru, a Co-Ni-Mg-Ce-Zr composite oxide and Al2O3. The gasoline engine tail gas purification three-way catalyst is low in price and can directly decompose a by-product NH3, so that emission of NH3 in tail gas is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of three-way catalysts, and in particular to a three-way catalyst for purifying exhaust gas from a gasoline engine and a preparation method thereof. Background Art

[0002] Exhaust treatment of vehicle gas engines is an important environmental issue, especially in the context of meeting the stringent National VI emission standards. Exhaust treatment of natural gas engines mainly relies on three-way catalysts (TWCs), which mainly use Pt-Pd-Rh precious metals as active components.

[0003] Rh catalytic reduction of NO in a three-way catalyst x The price of precious metal Rh has remained high for many years, and researchers have been looking for substitutes, and even used Pd, which had a relatively low cost before, to replace Rh, but at present, Rh has not been truly replaced in terms of performance and practical application. Hybrid vehicles are an ideal technical route in the transition period of pure electric vehicles to fully replace internal combustion engines, and are of great significance to energy conservation and emission reduction. At the current stage of National VI, the torque control and thermal management of mild hybrid models are relatively good, and the engine operating conditions of mild hybrid models are milder than those of traditional fuel models. The engine mostly works in a high-efficiency area and has low original emissions. During the cold start ignition stage, the engine can control a smaller torque output, which can reduce the emission quality in the cold stage, and the ignition performance and durability requirements of the three-way catalyst can also be reduced. Therefore, the use of low-cost active substances to replace Rh to achieve NO in the three-way catalyst x The reduction effect has become one of the research hotspots in the field of motor vehicle exhaust aftertreatment and has very important technical and economic significance.

[0004] In recent years, studies have found that gasoline vehicles produce a certain amount of NH during driving. 3 NH 3 The emissions will seriously affect the environment and human health. 3 Emissions are byproducts of the catalytic reaction of the three-way catalyst, mainly CO and H in the exhaust gas. 2 O reacts with water gas in the three-way catalytic converter to generate H 2 , H 2 Under the catalysis of Rh, some NO is over-catalyzed to reduce to NH 3 . Motor vehicle exhaust emissions are mainly in areas where people gather, which may be due to NH in urban areas. 3 Statistics show that in 2014, the NH 3 The total emission is about 1300t, accounting for the city's NH 3 Therefore, it is necessary to regulate the NH3 The National VII emission regulations for light gasoline vehicles that are being formulated may also include NH 3 Incorporate emission control indicators.

[0005] Therefore, the complete replacement of Rh and the enhancement of the three-way catalyst for NH 3 The treatment effect is a hot topic in the current research field of gasoline engine exhaust catalytic purification aftertreatment. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one object of the present invention is to propose a new three-way catalyst with low cost and reduced emission of NH3 in tail gas. According to the embodiments of the present invention, the preparation method of the present invention is simple and the steps are easy to operate. The present invention uses Pt and Pd as active components to form the first coating, and uses single Ru as the active component to form the second coating. The first and second coatings respectively use a new Ba-modified Al 2 O 3 The materials and Co-Ni-Mg-Ce-Zr composite oxide materials improve the catalytic effect of the active components. The second coating layer introduces Ru with a lower unit price to completely replace the expensive Rh, which greatly reduces the coating cost. At the same time, the formulation and process design of the first and second coating layers ensure the catalytic effect of the three-way catalyst. At the same time, the introduction of Ru and Co-Ni-Mg-Ce-Zr composite oxide can also achieve the by-product NH 3 Direct decomposition of NH 3 emissions.

[0007] In one aspect of the present invention, the present invention proposes a three-way catalyst for gasoline engine exhaust purification. According to an embodiment of the present invention, the gasoline engine exhaust purification three-way catalyst comprises a catalyst carrier and a coating coated on the carrier, the coating comprises a first coating and a second coating, the first coating comprises active components Pt, Pd and Ba modified Al 2 O 3 The second coating includes active components Ru, Co-Ni-Mg-Ce-Zr composite oxide and Al 2 O 3 The three-way catalyst for gasoline engine exhaust purification is low-cost and can achieve the by-product NH 3 Direct decomposition of NH 3 emissions.

[0008] According to an embodiment of the present invention, the above-mentioned gasoline engine exhaust purification three-way catalyst may further include at least one of the following additional technical features:

[0009] According to an embodiment of the present invention, the Ba-modified Al 2 O 3 BaO and Al in the material 2 O 3 The mass ratio of Pt to Pd is 0.1 to 0.2. The inventors found that within this ratio range, the thermal stability of Pt and Pd is improved, while below this ratio, the improvement of thermal stability is limited, and above this ratio range, the thermal stability of Al 2 O 3 The stability of the

[0010] According to an embodiment of the present invention, the Co-Ni-Mg-Ce-Zr composite oxide and Al in the second coating layer 2 O 3 The mass ratio of Al to Zn is 0.5 to 0.8. The inventors found that within this ratio range, the oxygen storage performance of the composite oxide is similar to that of Al 2 O 3 The ignition performance can be balanced. Below this range, the oxygen storage performance decreases, and above this range, the ignition performance will be affected to a certain extent.

[0011] According to an embodiment of the present invention, the mass ratio of Co, Ni, Mg, Ce and Zr in the Co-Ni-Mg-Ce-Zr composite oxide is (0.1-0.2):(0.1-0.2):(0.2-0.3):(1-2):(1-2). The inventors found that within this ratio range, the oxygen storage performance and the activity enhancement of Ru are both well promoted, and the performance is affected to a certain extent when it deviates from this range.

[0012] According to an embodiment of the present invention, the coating amount of the first coating layer is 60-80 g / L. The inventors have found that within this range, the best performance of the catalyst in the fresh state and the aged state can be balanced.

[0013] According to an embodiment of the present invention, the coating amount of the second coating layer is 80-100 g / L. The inventors have found that within this range, the best performance of the catalyst in the fresh state and the aged state can be balanced.

[0014] According to an embodiment of the present invention, the first coating layer covers the catalyst carrier, and the second coating layer covers the first coating layer.

[0015] According to an embodiment of the present invention, the catalyst carrier is a cordierite honeycomb ceramic carrier.

[0016] In another aspect of the present invention, the present invention also proposes a method for preparing a gasoline engine exhaust purification three-way catalyst. According to an embodiment of the present invention, the method comprises:

[0017] 1) Ba modified Al 2 O 3The material is mixed with water to obtain a first mixed solution, the first mixed solution is mixed with a modified precursor solution of Pt and Pd to obtain a second mixed solution, the second mixed solution is aged, and then aluminum sol is added to obtain a first coating slurry;

[0018] 2) coating the first coating slurry on a catalyst carrier, performing a first drying treatment and a first calcining treatment to obtain a catalyst carrier coated with a first coating;

[0019] 3) Co-Ni-Mg-Ce-Zr composite oxide, Al 2 O 3 Performing a third mixing process with water to obtain a third mixed solution, and performing a fourth mixing process on the third mixed solution and a modified precursor solution of Ru to obtain a second coating slurry;

[0020] 4) coating the second coating slurry onto the catalyst carrier coated with the first coating, performing a second drying treatment and a second calcination treatment to obtain the gasoline engine exhaust purification three-way catalyst. The method is simple to operate, low in price, and suitable for industrial mass production. The gasoline engine exhaust purification three-way catalyst obtained by the method can achieve the by-product NH 3 Direct decomposition of NH 3 emissions.

[0021] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:

[0022] According to an embodiment of the present invention, the Ba-modified Al 2 O 3 BaO and Al in the material 2 O 3 The mass ratio is 0.1~0.2.

[0023] According to an embodiment of the present invention, the Ba-modified Al 2 O 3 The material was prepared in the following way:

[0024] The barium acetate is dissolved in water to obtain a barium acetate solution, and the aluminum sol having a solid content of 30-40% and the barium acetate solution are subjected to a fourth mixing process, a drying process, and a third calcination process to obtain the Ba-modified Al 2 O 3 Materials, the BaO and Al 2 O 3 The mass ratio is 0.1~0.2.

[0025] According to an embodiment of the present invention, the drying process is performed by microwave drying.

[0026] According to an embodiment of the present invention, the drying rate after the drying process is >90%.

[0027] According to an embodiment of the present invention, the temperature of the third calcination treatment is 500-600°C.

[0028] According to an embodiment of the present invention, the third calcination treatment is performed for 2 to 4 hours.

[0029] According to an embodiment of the present invention, the solid content of the first mixed liquid is 30-40%.

[0030] According to an embodiment of the present invention, the D90 of the first mixed liquid is 8-15 μm.

[0031] According to an embodiment of the present invention, the second mixing treatment is performed by adding a modified precursor solution of Pt and Pd dropwise to the first mixed solution while stirring, and the dropping rate is controlled to be 5-6 mL / min.

[0032] According to an embodiment of the present invention, the temperature of the aging treatment is 60-80°C.

[0033] According to an embodiment of the present invention, the aging treatment time is 1 to 2 hours.

[0034] According to an embodiment of the present invention, the aluminum sol accounts for 1 to 3% of the mass of the solidified material of the second mixed solution after the aging treatment.

[0035] According to an embodiment of the present invention, the catalyst carrier is a cordierite honeycomb ceramic carrier.

[0036] According to an embodiment of the present invention, a coating amount of the first coating layer in the catalyst carrier coated with the first coating layer is 60 to 80 g / L.

[0037] According to an embodiment of the present invention, the temperature of the first drying process is 150-200°C.

[0038] According to an embodiment of the present invention, the drying rate of the first drying process is above 90%.

[0039] According to an embodiment of the present invention, the temperature of the first calcination treatment is 500-600°C.

[0040] According to an embodiment of the present invention, the time of the first calcination treatment is 2 to 4 hours.

[0041] According to an embodiment of the present invention, the coating amount of the second coating layer is 80-100 g / L.

[0042] According to an embodiment of the present invention, the temperature of the second drying process is 150-200°C.

[0043] According to an embodiment of the present invention, the drying rate of the second drying process is above 90%.

[0044] According to an embodiment of the present invention, the temperature of the second calcination treatment is 500-600°C.

[0045] According to an embodiment of the present invention, the time of the second calcination treatment is 2 to 4 hours.

[0046] According to an embodiment of the present invention, the Co-Ni-Mg-Ce-Zr composite oxide and Al 2 O 3 The mass ratio is 0.5 to 0.8.

[0047] According to an embodiment of the present invention, the mass ratio of Co, Ni, Mg, Ce and Zr in the Co-Ni-Mg-Ce-Zr composite oxide is (0.1-0.2):(0.1-0.2):(0.2-0.3):(1-2):(1-2).

[0048] According to an embodiment of the present invention, the Co-Ni-Mg-Ce-Zr composite oxide is prepared by the following method:

[0049] Cobalt nitrate, nickel nitrate, magnesium nitrate and cerium nitrate are dissolved in water, and then zirconium sol with a solid content of 30-40% is added to obtain a mixed solution, which is then dried and calcined for the fifth time to obtain the Co-Ni-Mg-Ce-Zr composite oxide.

[0050] According to an embodiment of the present invention, the drying process is performed by microwave drying.

[0051] According to an embodiment of the present invention, the drying rate of the drying process is >90%.

[0052] According to an embodiment of the present invention, the temperature of the fifth calcination process is 500-600°C.

[0053] According to an embodiment of the present invention, the fifth calcination treatment is performed for 2 to 4 hours.

[0054] In another aspect of the present invention, the present invention also proposes a gasoline engine exhaust purification three-way catalyst. According to an embodiment of the present invention, the gasoline engine exhaust purification three-way catalyst comprises a cordierite honeycomb ceramic carrier, a first coating coated on the cordierite honeycomb carrier, and a second coating coated on the first coating; the first coating comprises Pt, Pd noble metal active components and Ba modified Al 2 O 3The second coating comprises Ru noble metal active components, Co-Ni-Mg-Ce-Zr composite oxide and Al 2 O 3 .

[0055] According to an embodiment of the present invention, the above-mentioned gasoline engine exhaust purification three-way catalyst may further include at least one of the following additional technical features:

[0056] According to an embodiment of the present invention, the Ba-modified Al in the first coating layer 2 O 3 Materials, including BaO and Al 2 O 3 The mass ratio is 0.1~0.2.

[0057] According to an embodiment of the present invention, the Co-Ni-Mg-Ce-Zr composite oxide and Al in the second coating layer 2 O 3 The mass ratio is 0.5 to 0.8.

[0058] According to an embodiment of the present invention, the mass ratio of Co:Ni:Mg:Ce:Zr in the Co-Ni-Mg-Ce-Zr composite oxide in the second coating layer is 0.1-0.2:0.1-0.2:0.2-0.3:1-2:1-2.

[0059] According to an embodiment of the present invention, the coating amount of the first coating layer is 60-80 g / L; the coating amount of the second coating layer is 80-100 g / L.

[0060] In another aspect of the present invention, the present invention also proposes a method for preparing a three-way catalyst for purifying exhaust gas from a gasoline engine. According to an embodiment of the present invention, the method comprises the following steps:

[0061] (1) Ba-modified Al 2 O 3 Preparation of materials: Add barium acetate into sufficient deionized water and stir to dissolve. 2 O 3 The mass ratio of 0.1 to 0.2 is calculated, and aluminum sol with a solid content of 30 to 40% is added to the above barium acetate solution and fully stirred and mixed. The above mixture is then microwave dried. The drying is completed when the drying rate is greater than 90%. The powder is then calcined at 500 to 600° C. for 2 to 4 hours to obtain Ba-modified Al 2 O 3 Material;

[0062] (2) Preparation of the first coating slurry: The solution prepared in step (1) is mixed with deionized water to prepare a slurry, the amount of deionized water added is controlled so that the solid content of the slurry is 30-40%, and then the slurry is ball-milled so that the D90 of the slurry is 8-15 μm. The modified precursor solution of Pt and Pd is added dropwise while the slurry is stirred, and the dropping rate is controlled at 5-6 mL / min. After the dropping is completed, the slurry is placed in an environment of 60-80° C. for 1-2 h, and 1-3% of aluminum sol is added relative to the mass of the slurry solidified material to obtain the first coating slurry;

[0063] (3) Preparation of the first coating layer: the first coating slurry prepared in step (2) is applied to the inner wall pores of the cordierite honeycomb ceramic carrier. After the coating is completed, the cordierite honeycomb ceramic carrier is quickly dried at 150-200° C. to ensure that the drying rate is above 90%. The cordierite honeycomb ceramic carrier is then calcined at 500-600° C. for 2-4 hours to complete the coating preparation of the first coating layer.

[0064] (4) Preparation of Co-Ni-Mg-Ce-Zr composite oxide: Dissolve cobalt nitrate, nickel nitrate, magnesium nitrate and cerium nitrate in sufficient deionized water, stir evenly, add zirconium sol with a solid content of 30-40% and continue to mix and stir evenly. In the above mixture, the mass ratio of Co: Ni: Mg: Ce: Zr is controlled to be 0.1-0.2: 0.1-0.2: 0.2-0.3: 1-2: 1-2. Subsequently, the above mixture is microwave dried, and the drying is completed when the drying rate is >90%. After that, the powder is placed at 500-600°C and roasted for 2-4h to obtain Co-Ni-Mg-Ce-Zr composite oxide;

[0065] (5) Preparation of the second coating slurry: The Co-Ni-Mg-Ce-Zr composite oxide prepared in step (4) and Al 2 O 3 The mixture is mixed at a mass ratio of 0.5 to 0.8, and deionized water is added to prepare a slurry. The amount of deionized water added is controlled so that the solid content of the slurry is 20 to 30%. The slurry is then ball-milled to make the slurry D90 10 to 20 μm. The modified precursor solution of Ru is added dropwise while the slurry is stirred. The dropwise addition rate is controlled at 0.5 to 1 mL / min. After the dropwise addition is completed, the slurry is aged at room temperature for 8 to 12 hours, and 1 to 3% of aluminum sol relative to the mass of the slurry solidified material is added to obtain a second coating slurry.

[0066] (6) Preparation of the second coating layer: The second coating slurry prepared in step (5) is applied to the inner wall pores of the cordierite honeycomb ceramic carrier coated with the first coating layer prepared in step (3). After the coating is completed, the cordierite honeycomb ceramic carrier is quickly dried at 150-200° C. to ensure that the drying rate is above 90%. The cordierite honeycomb ceramic carrier is then calcined at 500-600° C. for 2-4 hours to complete the preparation of the second coating layer.

[0067] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:

[0068] According to an embodiment of the present invention, the Al sol in steps (2) and (5) has a solid content of 20-30%.

[0069] According to an embodiment of the present invention, the Pt and Pd modified precursor solution in step (2) is a platinum nitrate and palladium nitrate solution to which acetic acid is added, and the amount of acetic acid added is 5-10% of the mass of the Pt and Pd single substances.

[0070] According to an embodiment of the present invention, the modified precursor solution of Ru in step (5) is a ruthenium nitrate solution to which oxalic acid is added, and the amount of oxalic acid added is 5-15% of the mass of the Ru element.

[0071] According to an embodiment of the present invention, the Al in step (5) 2 O 3 Its crystal form is γ phase, and its specific surface area is 100~200m 2 / g.

[0072] According to the embodiments of the present invention, the preparation method of the present invention is simple and the steps are easy to operate.

[0073] According to the embodiment of the present invention, the present invention uses Pt and Pd as active components to form the first coating layer, and uses Ru as the active component to form the second coating layer. The first and second coating layers respectively use the new Ba-modified Al 2 O 3 The materials and Co-Ni-Mg-Ce-Zr composite oxide materials improve the catalytic effect of the active components. The second coating layer introduces Ru with a lower unit price to completely replace the expensive Rh, which greatly reduces the coating cost. At the same time, the formulation and process design of the first and second coating layers ensure the catalytic effect of the three-way catalyst. At the same time, the introduction of Ru and Co-Ni-Mg-Ce-Zr composite oxide can also achieve the by-product NH 3 Direct decomposition of NH 3 emissions. DETAILED DESCRIPTION

[0074] The embodiments described below are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0075] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0076] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0077] Embodiment 1:

[0078] A three-way catalyst for purifying exhaust gas from a gasoline engine, comprising a cordierite honeycomb ceramic carrier, with a specification of 118.4 mm × 152.4 mm, a pore density of 750 cpsi, a pore wall thickness of 2 mil, and a volume of 1.678 L; the carrier is coated with a first coating and a second coating, the coating amount of the first coating is 60 g / L; the coating amount of the second coating is 80 g / L. The first coating includes Pt and Pd precious metal active components, and the content of Pt is 30 g / ft 3 ; Pd: 30g / ft 3 The second coating includes a Ru precious metal active component, the content of which is Ru: 20g / ft 3 .

[0079] The preparation method of a three-way catalyst for purifying exhaust gas from a gasoline engine comprises the following steps:

[0080] (1) Ba-modified Al 2 O 3 Preparation of materials: Add barium acetate into sufficient deionized water and stir to dissolve. 2 O 3 The mass ratio of 0.1 was calculated, and aluminum sol with a solid content of 30% was added to the above barium acetate solution and fully stirred and mixed. The above mixture was then microwave dried. The drying was completed when the drying rate was 95%. After that, the powder was calcined at 500°C for 4h to obtain Ba-modified Al 2 O 3 Material;

[0081] (2) Preparation of the first coating slurry: The Ba-modified Al prepared in step (1) 2 O 3The material is mixed with deionized water to prepare a slurry, and the amount of deionized water added is controlled to make the solid content of the slurry 30%, and then the slurry is ball-milled to make the slurry D90 8μm, and platinum nitrate and palladium nitrate solutions doped with acetic acid are added dropwise while the slurry is stirred, wherein the amount of acetic acid added is 5% of the mass of the Pt and Pd single substances, and the dropping rate is controlled at 5mL / min. After the dropping is completed, the slurry is placed at 60°C for aging for 2h, and 1% of aluminum sol (solid content of aluminum sol is 20%) relative to the mass of the slurry solidified material is added to obtain a first coating slurry;

[0082] (3) Preparation of the first coating layer: The first coating slurry prepared in step (2) is applied to the inner wall pores of the cordierite honeycomb ceramic carrier. After the coating is completed, the cordierite honeycomb ceramic carrier is quickly dried at 150° C. with a drying rate of 93%. The cordierite honeycomb ceramic carrier is then calcined at 500° C. for 4 h to complete the preparation of the first coating layer.

[0083] (4) Preparation of Co-Ni-Mg-Ce-Zr composite oxide: Dissolve cobalt nitrate, nickel nitrate, magnesium nitrate and cerium nitrate in sufficient deionized water, stir evenly, add zirconium sol with a solid content of 30% and continue to mix and stir evenly. In the above mixture, the mass ratio of Co: Ni: Mg: Ce: Zr is controlled to be 0.1: 0.1: 0.2: 1: 1. Subsequently, the above mixture is microwave dried, and the drying is completed when the drying rate is 92%. After that, the powder is placed at 500°C for 4 hours to obtain Co-Ni-Mg-Ce-Zr composite oxide.

[0084] (5) Preparation of the second coating slurry: The Co-Ni-Mg-Ce-Zr composite oxide prepared in step (4) and the γ-phase Al 2 O 3 Mix them in a mass ratio of 0.5. 2 O 3 The specific surface area is 100m 2 / g, then add deionized water to prepare slurry, control the amount of deionized water added to make the slurry solid content at 20%, then ball mill the slurry to make the slurry D90 at 10μm, dropwise add ruthenium nitrate solution doped with oxalic acid while the slurry is stirred, wherein the amount of oxalic acid added is 5% of the mass of Ru elemental substance, and the dropwise acceleration rate is controlled at 0.5mL / min. After the dropwise addition is completed, the slurry is aged at room temperature for 8h, and 1% of aluminum sol (solid content of aluminum sol is 20%) relative to the mass of the slurry solidified material is added to obtain a second coating slurry;

[0085] (6) Preparation of the second coating layer: The second coating slurry prepared in step (5) is applied to the inner wall pores of the cordierite honeycomb ceramic carrier coated with the first coating layer prepared in step (3). After the coating is completed, the cordierite honeycomb ceramic carrier is quickly dried at 150° C. with a drying rate of 93%. The cordierite honeycomb ceramic carrier is then calcined at 500° C. for 4 h to complete the preparation of the second coating layer.

[0086] Embodiment 2:

[0087] A three-way catalyst for purifying exhaust gas from a gasoline engine, comprising a cordierite honeycomb ceramic carrier, with a specification of 118.4 mm × 152.4 mm, a pore density of 750 cpsi, a pore wall thickness of 2 mil, and a volume of 1.678 L; the carrier is coated with a first coating and a second coating, the coating amount of the first coating is 80 g / L; the coating amount of the second coating is 100 g / L. The first coating includes Pt and Pd precious metal active components, and the content of Pt is 30 g / ft 3 ; Pd: 30g / ft 3 The second coating includes a Ru precious metal active component, the content of which is Ru: 20g / ft 3 .

[0088] The preparation method of a three-way catalyst for purifying exhaust gas from a gasoline engine comprises the following steps:

[0089] (1) Ba-modified Al 2 O 3 Preparation of materials: Add barium acetate into sufficient deionized water and stir to dissolve. 2 O 3 The mass ratio of 0.2 was calculated, and aluminum sol with a solid content of 40% was added to the above barium acetate solution and fully stirred and mixed. The above mixture was then microwave dried. The drying was completed when the drying rate was 94%. After that, the powder was calcined at 600°C for 2h to obtain Ba-modified Al 2 O 3 Material;

[0090] (2) Preparation of the first coating slurry: The Ba-modified Al prepared in step (1) 2 O 3 The material is mixed with deionized water to prepare a slurry, and the amount of deionized water added is controlled to make the solid content of the slurry 40%, and then the slurry is ball-milled to make the slurry D90 at 15 μm, and platinum nitrate and palladium nitrate solutions doped with acetic acid are added dropwise while the slurry is stirred, wherein the amount of acetic acid added is 10% of the mass of the Pt and Pd single substances, and the dropping rate is controlled at 6 mL / min. After the dropping is completed, the slurry is placed in an environment of 80° C. for aging for 1 hour, and 3% of aluminum sol (solid content of aluminum sol is 30%) relative to the mass of the slurry solidified material is added to obtain a first coating slurry;

[0091] (3) Preparation of the first coating layer: The first coating slurry prepared in step (2) is applied to the inner wall pores of the cordierite honeycomb ceramic carrier. After the coating is completed, the cordierite honeycomb ceramic carrier is quickly dried at 200° C. with a drying rate of 92%. The cordierite honeycomb ceramic carrier is then calcined at 600° C. for 2 h to complete the coating preparation of the first coating layer.

[0092] (4) Preparation of Co-Ni-Mg-Ce-Zr composite oxide: Dissolve cobalt nitrate, nickel nitrate, magnesium nitrate and cerium nitrate in sufficient deionized water, stir evenly, add zirconium sol with a solid content of 40% and continue to mix and stir evenly. In the above mixture, the mass ratio of Co: Ni: Mg: Ce: Zr is controlled to be 0.2: 0.2: 0.3: 2: 2. Subsequently, the above mixture is microwave dried, and the drying is completed when the drying rate is 95%. After that, the powder is placed at 600°C for 2h to obtain Co-Ni-Mg-Ce-Zr composite oxide.

[0093] (5) Preparation of the second coating slurry: The Co-Ni-Mg-Ce-Zr composite oxide prepared in step (4) and the γ-phase Al 2 O 3 Mix them in a mass ratio of 0.8. 2 O 3 The specific surface area is 200m 2 / g, then add deionized water to prepare slurry, control the amount of deionized water added to make the slurry solid content at 30%, then ball mill the slurry to make the slurry D90 at 20μm, dropwise add ruthenium nitrate solution doped with oxalic acid while the slurry is stirred, wherein the amount of oxalic acid added is 15% of the mass of Ru elemental substance, and the dropwise acceleration rate is controlled at 1mL / min. After the dropwise addition is completed, the slurry is aged at room temperature for 12h, and 3% of aluminum sol (solid content of aluminum sol is 30%) relative to the mass of the slurry solidified material is added to obtain a second coating slurry;

[0094] (6) Preparation of the second coating layer: The second coating slurry prepared in step (5) is applied to the inner wall pores of the cordierite honeycomb ceramic carrier coated with the first coating layer prepared in step (3). After the coating is completed, the cordierite honeycomb ceramic carrier is quickly dried at 200° C. with a drying rate of 92%. The cordierite honeycomb ceramic carrier is then calcined at 600° C. for 2 h to complete the preparation of the second coating layer.

[0095] Embodiment 3:

[0096] A three-way catalyst for purifying exhaust gas from a gasoline engine, comprising a cordierite honeycomb ceramic carrier, with a specification of 118.4 mm × 152.4 mm, a pore density of 750 cpsi, a pore wall thickness of 2 mil, and a volume of 1.678 L; the carrier is coated with a first coating and a second coating, the coating amount of the first coating is 60 g / L; the coating amount of the second coating is 100 g / L. The first coating includes Pt and Pd precious metal active components, and the content of Pt is 30 g / ft 3 ; Pd: 30g / ft 3 The second coating includes a Ru precious metal active component, the content of which is Ru: 20g / ft 3 .

[0097] The preparation method of a three-way catalyst for purifying exhaust gas from a gasoline engine comprises the following steps:

[0098] (1) Ba-modified Al 2 O 3 Preparation of materials: Add barium acetate into sufficient deionized water and stir to dissolve. 2 O 3 The mass ratio of 0.15 was calculated, and aluminum sol with a solid content of 35% was added to the above barium acetate solution and fully stirred and mixed. Then the above mixture was microwave dried. The drying was completed when the drying rate was 95%. Then the powder was calcined at 550°C for 3h to obtain Ba-modified Al 2 O 3 Material;

[0099] (2) Preparation of the first coating slurry: The Ba-modified Al prepared in step (1) 2 O 3 The material is mixed with deionized water to prepare a slurry, and the amount of deionized water added is controlled to make the solid content of the slurry 35%, and then the slurry is ball-milled to make the slurry D90 12 μm, and platinum nitrate and palladium nitrate solutions doped with acetic acid are added dropwise while the slurry is stirred, wherein the amount of acetic acid added is 8% of the mass of Pt and Pd single substances, and the dropping rate is controlled at 6 mL / min. After the dropping is completed, the slurry is placed in an environment of 70° C. for aging for 1 hour, and 2% of aluminum sol (solid content of aluminum sol is 25%) relative to the mass of the slurry solidified material is added to obtain a first coating slurry;

[0100] (3) Preparation of the first coating layer: The first coating slurry prepared in step (2) is applied to the inner wall pores of the cordierite honeycomb ceramic carrier. After the coating is completed, the cordierite honeycomb ceramic carrier is quickly dried at 180° C. with a drying rate of 93%. The cordierite honeycomb ceramic carrier is then calcined at 550° C. for 3 h to complete the coating preparation of the first coating layer.

[0101] (4) Preparation of Co-Ni-Mg-Ce-Zr composite oxide: Dissolve cobalt nitrate, nickel nitrate, magnesium nitrate and cerium nitrate in sufficient deionized water, stir evenly, add zirconium sol with a solid content of 35% and continue to mix and stir evenly. In the above mixture, the mass ratio of Co: Ni: Mg: Ce: Zr is controlled to be 0.15: 0.15: 0.25: 1.5: 1.5. Subsequently, the above mixture is microwave dried, and the drying is completed when the drying rate is 96%. After that, the powder is placed at 550°C for 3 hours to obtain Co-Ni-Mg-Ce-Zr composite oxide.

[0102] (5) Preparation of the second coating slurry: The Co-Ni-Mg-Ce-Zr composite oxide prepared in step (4) and the γ-phase Al 2 O 3 Mix them in a mass ratio of 0.6. 2 O 3 The specific surface area is 150m 2 / g, then add deionized water to prepare slurry, control the amount of deionized water added to make the slurry solid content at 25%, then ball mill the slurry to make the slurry D90 at 15μm, dropwise add ruthenium nitrate solution doped with oxalic acid while the slurry is stirred, wherein the amount of oxalic acid added is 10% of the mass of Ru elemental substance, and the dropwise acceleration rate is controlled at 1mL / min. After the dropwise addition is completed, the slurry is aged at room temperature for 10h, and 2% of aluminum sol (solid content of aluminum sol is 25%) relative to the mass of the slurry solidified material is added to obtain a second coating slurry;

[0103] (6) Preparation of the second coating layer: The second coating slurry prepared in step (5) is applied to the inner wall pores of the cordierite honeycomb ceramic carrier coated with the first coating layer prepared in step (3). After the coating is completed, the cordierite honeycomb ceramic carrier is quickly dried at 180° C. with a drying rate of 94%. The cordierite honeycomb ceramic carrier is then calcined at 550° C. for 3 h to complete the preparation of the second coating layer.

[0104] Embodiment 4:

[0105] A three-way catalyst for purifying exhaust gas from a gasoline engine, comprising a cordierite honeycomb ceramic carrier, with a specification of 118.4 mm × 152.4 mm, a pore density of 750 cpsi, a pore wall thickness of 2 mil, and a volume of 1.678 L; the carrier is coated with a first coating and a second coating, the coating amount of the first coating is 80 g / L; the coating amount of the second coating is 80 g / L. The first coating includes Pt and Pd precious metal active components, and the content of Pt is 30 g / ft 3 ; Pd: 30g / ft 3 The second coating includes a Ru precious metal active component, the content of which is Ru: 20g / ft 3 .

[0106] The preparation method of a three-way catalyst for purifying exhaust gas from a gasoline engine comprises the following steps:

[0107] (1) Ba-modified Al 2 O 3 Preparation of materials: Add barium acetate into sufficient deionized water and stir to dissolve. 2 O 3 The mass ratio of 0.16 was calculated, and aluminum sol with a solid content of 37% was added to the above barium acetate solution and fully stirred and mixed. The above mixture was then microwave dried. The drying was completed when the drying rate was 95%. After that, the powder was calcined at 550°C for 3h to obtain Ba-modified Al 2 O 3 Material;

[0108] (2) Preparation of the first coating slurry: The Ba-modified Al prepared in step (1) 2 O 3 The material is mixed with deionized water to prepare a slurry, and the amount of deionized water added is controlled to make the solid content of the slurry 30%, and then the slurry is ball-milled to make the slurry D90 at 13 μm, and platinum nitrate and palladium nitrate solutions doped with acetic acid are added dropwise while the slurry is stirred, wherein the amount of acetic acid added is 7% of the mass of the Pt and Pd single substances, and the dropping rate is controlled at 6 mL / min. After the dropping is completed, the slurry is placed at 70° C. for aging for 2 hours, and 2% of aluminum sol (solid content of aluminum sol is 25%) relative to the mass of the slurry solidified material is added to obtain a first coating slurry;

[0109] (3) Preparation of the first coating layer: The first coating slurry prepared in step (2) is applied to the inner wall pores of the cordierite honeycomb ceramic carrier. After the coating is completed, the cordierite honeycomb ceramic carrier is quickly dried at 160° C. with a drying rate of 92%. The cordierite honeycomb ceramic carrier is then calcined at 550° C. for 4 h to complete the coating preparation of the first coating layer.

[0110] (4) Preparation of Co-Ni-Mg-Ce-Zr composite oxide: Dissolve cobalt nitrate, nickel nitrate, magnesium nitrate and cerium nitrate in sufficient deionized water, stir evenly, add zirconium sol with a solid content of 30% and continue to mix and stir evenly. In the above mixture, the mass ratio of Co: Ni: Mg: Ce: Zr is controlled to be 0.15: 0.15: 0.2: 2: 1.5. Subsequently, the above mixture is microwave dried, and the drying is completed when the drying rate is 96%. After that, the powder is placed at 550°C for 3 hours to obtain Co-Ni-Mg-Ce-Zr composite oxide.

[0111] (5) Preparation of the second coating slurry: The Co-Ni-Mg-Ce-Zr composite oxide prepared in step (4) and the γ-phase Al 2 O 3Mix them in a mass ratio of 0.7. 2 O 3 The specific surface area is 180m 2 / g, then add deionized water to prepare slurry, control the amount of deionized water added to make the slurry solid content at 24%, then ball mill the slurry to make the slurry D90 at 16μm, dropwise add ruthenium nitrate solution doped with oxalic acid while the slurry is stirred, wherein the amount of oxalic acid added is 12% of the mass of Ru elemental substance, and the dropwise acceleration rate is controlled at 1mL / min. After the dropwise addition is completed, the slurry is aged at room temperature for 9h, and 2% of aluminum sol (solid content of aluminum sol is 30%) relative to the mass of the slurry solidified material is added to obtain a second coating slurry;

[0112] (6) Preparation of the second coating layer: The second coating slurry prepared in step (5) is applied to the inner wall pores of the cordierite honeycomb ceramic carrier coated with the first coating layer prepared in step (3). After the coating is completed, the cordierite honeycomb ceramic carrier is quickly dried at 160° C. with a drying rate of 93%. The cordierite honeycomb ceramic carrier is then calcined at 550° C. for 4 h to complete the preparation of the second coating layer.

[0113] Comparative Example 1:

[0114] Comparative Example 1 is a commercial three-way catalyst used in the "National VI b" stage, and its carrier size and specifications are the same as those of Examples 1 to 4. The Pt and Pd precious metal contents of Comparative Example 1 are the same as those of Examples 1 to 4, and the Rh content is 4g / ft 3 , does not contain Ru components.

[0115] Performance comparison test:

[0116] The three-way catalysts corresponding to Examples 1 to 4 and Comparative Example 1 were respectively packaged into exhaust purifiers and installed in the exhaust system of a 1.5T National VI light gasoline vehicle (first category vehicle), with the installation position being close-coupled. Then, a Type I test specified in GB18352.6-2016 was carried out on the vehicle hub to compare the fresh CO, THC, and NO of each solution. x and NH 3 Gaseous pollutant emissions. After that, the catalysts of each scheme were installed on the gasoline engine bench and subjected to standard bench cycle (SBC) aging according to GB18352.6-2016 requirements, with an aging time of 200 hours. After aging, the catalysts of each scheme were installed in the exhaust system of a 1.5T displacement National VI light gasoline vehicle mentioned above, and the Type I test specified in GB18352.6-2016 was carried out on the vehicle hub. The emission comparison test results are shown in Table 1.

[0117] Table 1 Comparison of gaseous pollutant emissions from Type I tests of various schemes

[0118]

[0119] As shown in Table 1, the fresh and aged CO, THC and NO of the catalysts of Examples 1 to 4 prepared by the present invention are x The pollutant emission values ​​are basically the same as those of Comparative Example 1, and both meet the National VI (b) limit requirements. 3 The emission is also significantly lower than that of Comparative Example 1. Since the present invention uses Ru and Co-Ni-Mg-Ce-Zr composite oxide as the active components of the second coating, it is well ensured that the coating is effective in NOx without using expensive Rh metal. x The conversion efficiency of NH 3 Effectively decomposes and reduces NH 3 Since the price of Ru is only about one tenth of that of Rh, when the content of precious metals Pt and Pd is the same in Examples 1 to 4 and Comparative Example 1, the total price of Ru in the former is only about half of that in the latter, thereby significantly reducing the coating cost.

[0120] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

Claims

1. A three-way catalyst for purifying exhaust gas from a gasoline engine, characterized in that: It includes a catalyst carrier and a coating coated on the carrier, wherein the coating includes a first coating and a second coating, wherein the first coating includes active components Pt, Pd and Ba-modified Al2O3 material, and the second coating includes active components Ru, Co-Ni-Mg-Ce-Zr composite oxide and Al2O3.

2. The three-way catalyst for purifying gasoline engine exhaust gas according to claim 1, characterized in that: The mass ratio of BaO to Al2O3 in the Ba-modified Al2O3 material is 0.1 to 0.

2.

3. The three-way catalyst for purifying gasoline engine exhaust gas according to claim 1, characterized in that: The mass ratio of Co-Ni-Mg-Ce-Zr composite oxide to Al2O3 in the second coating layer is 0.5-0.

8.

4. The three-way catalyst for purifying gasoline engine exhaust gas according to claim 1, characterized in that: The mass ratio of Co, Ni, Mg, Ce and Zr in the Co-Ni-Mg-Ce-Zr composite oxide is (0.1-0.2):(0.1-0.2):(0.2-0.3):(1-2):(1-2).

5. The three-way catalyst for purifying gasoline engine exhaust gas according to claim 1, characterized in that: The coating amount of the first coating is 60-80 g / L; Optionally, the coating amount of the second coating is 80 to 100 g / L; Optionally, the first coating layer covers the catalyst support, and the second coating layer covers the first coating layer; Optionally, the catalyst carrier is a cordierite honeycomb ceramic carrier.

6. A method for preparing a three-way catalyst for purifying gasoline engine exhaust, characterized in that: include: 1) mixing the Ba-modified Al2O3 material with water to obtain a first mixed solution, performing a second mixing process on the first mixed solution and a modified precursor solution of Pt and Pd to obtain a second mixed solution, performing an aging process on the second mixed solution, and then adding aluminum sol to obtain a first coating slurry; 2) coating the first coating slurry on a catalyst carrier, performing a first drying treatment and a first calcining treatment to obtain a catalyst carrier coated with a first coating; 3) performing a third mixing treatment on the Co-Ni-Mg-Ce-Zr composite oxide, Al2O3 and water to obtain a third mixed solution, and performing a fourth mixing treatment on the third mixed solution and a modified precursor solution of Ru to obtain a second coating slurry; 4) coating the second coating slurry onto the catalyst carrier coated with the first coating, performing a second drying treatment and a second calcination treatment to obtain the gasoline engine exhaust purification three-way catalyst.

7. The method according to claim 6, characterized in that The mass ratio of BaO to Al2O3 in the Ba-modified Al2O3 material is 0.1 to 0.2; Optionally, the Ba-modified Al2O3 material is prepared by: Dissolving barium acetate in water to obtain a barium acetate solution, subjecting an aluminum sol having a solid content of 30 to 40% and the barium acetate solution to a fourth mixing process, a drying process, and a third calcination process to obtain the Ba-modified Al2O3 material, wherein the mass ratio of BaO to Al2O3 is 0.1 to 0.2; Optionally, the drying process is performed by microwave drying; Optionally, the drying rate after the drying treatment is >90%; Optionally, the temperature of the third calcination treatment is 500-600°C; Optionally, the third calcination treatment is performed for 2 to 4 hours.

8. The method according to claim 6, characterized in that The solid content of the first mixed solution is 30-40%; Optionally, the D90 of the first mixed solution is 8 to 15 μm; Optionally, the second mixing treatment is performed by adding a modified precursor solution of Pt and Pd dropwise to the first mixed solution under stirring, and the dropping rate is controlled to be 5 to 6 mL / min; Optionally, the temperature of the aging treatment is 60 to 80°C; Optionally, the aging treatment time is 1 to 2 hours; Optionally, the aluminum sol accounts for 1 to 3% of the mass of the solidified material of the second mixed solution after the aging treatment.

9. The method according to claim 6, characterized in that The catalyst carrier is a cordierite honeycomb ceramic carrier; Optionally, the coating amount of the first coating layer in the catalyst carrier coated with the first coating layer is 60 to 80 g / L; Optionally, the temperature of the first drying treatment is 150-200°C; Optionally, the drying rate of the first drying treatment is above 90%; Optionally, the temperature of the first calcination treatment is 500-600°C; Optionally, the first calcination treatment time is 2 to 4 hours; Optionally, the coating amount of the second coating is 80 to 100 g / L; Optionally, the temperature of the second drying treatment is 150-200°C; Optionally, the drying rate of the second drying treatment is above 90%; Optionally, the temperature of the second calcination treatment is 500-600°C; Optionally, the second calcination treatment is performed for 2 to 4 hours.

10. The method according to claim 6, characterized in that The mass ratio of the Co-Ni-Mg-Ce-Zr composite oxide to Al2O3 is 0.5 to 0.8; Optionally, the mass ratio of Co, Ni, Mg, Ce and Zr in the Co-Ni-Mg-Ce-Zr composite oxide is (0.1-0.2):(0.1-0.2):(0.2-0.3):(1-2):(1-2); Optionally, the Co-Ni-Mg-Ce-Zr composite oxide is prepared by the following method: Dissolving cobalt nitrate, nickel nitrate, magnesium nitrate and cerium nitrate in water, then adding zirconium sol with a solid content of 30-40% to obtain a mixed solution, and then performing a drying process and a fifth calcination process to obtain the Co-Ni-Mg-Ce-Zr composite oxide; Optionally, the drying process is performed by microwave drying; Optionally, the drying rate of the drying process is >90%; Optionally, the temperature of the fifth calcination treatment is 500-600°C; Optionally, the fifth calcination treatment is performed for 2 to 4 hours.

Citation Information

Patent Citations

  • Electrospray SCR diesel engine tail gas catalyst

    CN102580761A

  • Three-way catalyst used for automobile emission purification and preparation method thereof

    CN103433057A

  • Catalyst for gas-fueled vehicle tail gas treatment and preparation method thereof

    CN106268859A

  • Ammoxidation catalyst for diesel engine exhaust gas purification system and preparation method thereof

    CN106902864A

  • Preparation method of three-way catalyst with high CO purification capability and catalyst of preparation method

    CN109876793A